PENGEMBANGAN BAHAN AJAR BERBASIS SCRATCH UNTUK MENINGKATKAN KEMAMPUAN NUMERASI DAN BELIEF MATEMATIS - Nurjaman, Cecep Ali; Supratman; Rahayu, Diar Veni (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
Numeracy is a basic skill needed by learners to solve problems using the concept of numbers. This research is based on low numeracy skills and mathematical beliefs of VIII A SMPN 1 Bojongasih students. This study aims to determine how the development of Scratch-based teaching materials can improve the numeracy skills and mathematical beliefs of students. This research is a development research using the ADDIE model. At the analysis stage, researchers conducted a needs analysis, curriculum analysis, student character analysis, school environment analysis and technology analysis. At the design stage, researchers collected data, made flowcharts, story boards, collected media making materials, prepared teaching materials, designed test instruments, compiled validation sheets, made user response questionnaires and mathematical belief questionnaires. At the Development stage, researchers produce products that have been designed and validate material experts and media experts with validation results in the “very feasible to use” category. At the Implementation stage, teaching materials are applied to sample class students and get a positive response in the “very good” category. At the evaluation stage, teaching materials are applied in learning activities to 32 students. User response to Scratch-based teaching materials is positive with a “very good” category. N-Gain results obtained in the “medium” category. Effect Size (ES) test results obtained in the “Strong Effect” category. The score of the main dimensions of belief about mathematics education, belief about oneself and belief about the social context is in the “High” category. So it can be concluded that Scratch-based teaching materials can improve students' numeracy skills and mathematical beliefs.